Effects of Light Sources and Intensity on Broilers Grown to Heavy Weights: Hematophysiological and Biochemical Assessment - Olanrewaju , Hammed A.; Collier, Stephanie D.; Purswell, Joseph L.; Branton, Scott L. (International Journal of Poultry Science, 2016)
Background: Most governments around the world including the USA have passed measures to phase out incandescent light bulbs in favor of more energy-efficient lighting alternatives. Research is limited on blood physiological variables of broilers grown to heavy weights (>3 kg) under these new light sources to ensure health and welfare of broilers. Objective: We investigated the effects of light sources and intensity on blood physiological and biochemical variables of broilers grown to heavy weights. Methodology: In each of 4 trials having 2 replicates per trial, 960 1 day old ross×ross 708 chicks were randomly distributed into 16 rooms (30 male and 30 female per room). A 4×2 factorial treatment structure evaluated 4 light sources [incandescent (ICD, standard), compact fluorescent (CFL), Light Emitting Diode (LED) and poultry specific filtered LED (PSF-LED)] from day 1-56 and 2 levels of light intensities (5 and 20 lx) from day 22-56 of age at 50% RH. Feed and water were provided ad libitum. Blood samples were collected from wing brachial vein on day 14, 21, 28, 42 and day 56 of age and analyzed immediately. Results: Light sources had effect (p<0.05) on BW, pH, pCO2, pO2, SaO2, electrolytes, MCHC and Osmo. However, all these changes were still within the acid-base homeostasis and physiological ranges. There was no effect of light intensity and no difference between 5 and 20 lx on almost all examined variables. Plasma corticosterone and blood glucose concentrations were not affected by treatment. Conclusion: It was concluded that the light sources evaluated in this study might be suitable for replacement of ICD light source in commercial poultry facilities at the light intensities used in this study to reduce energy cost and optimize production efficiency without compromising welfare of broilers grown to heavy weights.